The Difference between the Perception and Expectations of the Hotel Management Students With Reference to Benefits and Challenges During Internship - Singh Rana, Varinder; Bathla, Gaurav (International Journal of Psychosocial Rehabilitation, 2020)
As we know that for any of the professional courses, across the world, internship is an integral part. This is because of the reason that the respective companies who recruit these professional believe that they will take the right decision for their respective companies. It can also be said that the placement of these professional is based on the kind and type of course they have pursued and the company in which undergone their internship. The same stands true even for the hotel industry; as a matter of fact the level internship is very crucial at the time of placement of the students. This present study assimilates the role of internship and relationship of the same with placement of student. Study is based on primary data, which is being collected by using a close ended questionnaire on 200 students of the private institutes and universities offering the course of hotel management. SPSS ver. 20.0 is used to analyze the collected data.